Facultative Liaison as a Formal Register Marker in French Oral Communication - Nani Kusrini; Sajarwa Sajarwa; B.R. Suryo Baskoro; Hayatul Cholsy (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
Language variations based on the level of formality in spoken communication are not only determined by particular words or morphosyntax but also phonological elements. The concept of formality itself is considered the most important dimension of the variety of styles or registers. This study aims to describe the forms of facultative liaison in present-day French communication and liaison consonants formed by the linking process, to explain whether facultative liaison is still a marker of formal variety, and to reveal the factors that influence its use. This research is a sociolinguistic study with qualitative data using 15 recorded speeches by several politicians (formal) and 21 vlogs from French YouTubers (informal) with a total duration of 6 hours. The results of this study show that facultative liaison is used much more in formal than non-formal communication. Most forms of facultative liaison are a series of verbs être + determinant, auxiliary verbs être/avoir + participe passé (past participle), noun + adjective. It can be concluded that the more formal the communication, the more facultative liaisons are used. The liaison consonant [t] appears the most often, and the dominant factors in the use of facultative liaison are stylistics including formality, shared knowledge, etc, the sensitivity of formality, and the linguistic intuition of the speaker.